Research and Artistic Expression of Sodium Alginate Dry Gel Film - Wenying CAO; Yukun SHAO; Zhen CAO; Fan YU; Jie YUAN (Pige Kexue Yu Gongcheng)
Sodium alginate (SA), a natural polysaccharide, is known for its biodegradability and excellent biocompatibility. SA gel film shows significant potential in creative fashion design, however, it has a drawback of insufficient strength. By incorporating gelatin (G) into SA at varying ratios for experimental production, a range of products with different proportions were crafted. The tensile strengths of three groups of products with m(SA)/m(G) ratios of 6∶2, 6∶3, and 6∶4, respectively, was analyzed, and finally, the artistic expression of these products was carried out. The research indicates that as the proportion of G increases, the tensile strength increases accordingly, and there are significant differences in the tensile strengths among the dry gel films made with different m(SA)/m(G) ratios. The artistic expression of dry SA gel film contributes materials for creative design, reinforcing the concept of sustainable development and environmental protection.